2018
DOI: 10.3390/educsci8020074
|View full text |Cite
|
Sign up to set email alerts
|

Learning Landscapes: Playing the Way to Learning and Engagement in Public Spaces

Abstract: Children from under-resourced communities regularly enter formal schooling lagging behind their peers. These deficits in areas such as language development, reading readiness, and even in the kind of spatial skills that predict later mathematical knowledge, may persist throughout their lifespan. To address such gaps, policymakers have focused largely on schooling as the great equalizer. Yet, children only spend 20% of their waking hours in school. How can developmental scientists and educators address this "ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(36 citation statements)
references
References 87 publications
0
32
0
2
Order By: Relevance
“…Previous research suggested that science board games should simulate students to apply scientific knowledge when dealing with life situations. Moreover, if the only topic that was gamified was the scientific concept, for middle school students who have studied only the basic concepts of chemistry, it is difficult to maintain interest in playing the games [15][16][17]. Therefore, there is still room for improvement in the current scientific board games in teaching the periodic table of the chemical elements.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research suggested that science board games should simulate students to apply scientific knowledge when dealing with life situations. Moreover, if the only topic that was gamified was the scientific concept, for middle school students who have studied only the basic concepts of chemistry, it is difficult to maintain interest in playing the games [15][16][17]. Therefore, there is still room for improvement in the current scientific board games in teaching the periodic table of the chemical elements.…”
Section: Introductionmentioning
confidence: 99%
“…We have written about the benefits of Learning Landscapes for children from low‐income families (Hassinger‐Das, Bustamante, Hirsh‐Pasek, & Golinkoff, ), but we also recognize the importance of these projects for all children. From a strengths‐based perspective, Learning Landscapes are meant to interact with families’ knowledge—the information and skills already present in their households (Moll, Amanti, Neff, & Gonzalez, )—to produce meaningful play and learning experiences for children in the places families spend time.…”
Section: A Public‐health Approach To Educationmentioning
confidence: 99%
“…In the first pilot study, children playing Parkopolis used significantly more STEM language (e.g., whole number, fraction, spatial, and measurement language); made more observations; and showed greater engagement, confidence, and persistence working with difficult problems than children in a control condition who were asked to invent their own game in an outdoor space (a proxy for what children may do at a park without Parkopolis; Hassinger‐Das, Bustamante, Hirsh‐Pasek, & Golinkoff, ). A larger version of Parkopolis is being tested at the Please Touch Museum in Philadelphia, Pennsylvania.…”
Section: Learning Landscapes Projectsmentioning
confidence: 99%
“…Research suggests that playful learning may be more beneficial to children than rote or directive learning practices (Golinkoff & Hirsh-Pasek, 2016) and can be especially beneficial in community settings because they support cohesion and ownership (Hassinger-Das, Bustamante, Hirsh-Pasek, & Golinkoff, 2018). Research further shows many children experience summer learning loss, but youth from low-income communities are especially affected by this "summer slide" (Cooper, Nye, Charlton, Lindsay, & Greathouse, 1996).…”
mentioning
confidence: 99%
“…In summary, the mechanism of the playful learning projects is to enhance caregiver-child social interaction by prompting caregivers to initiate targeted interactions filled with skill-building topics with their children during moments that would otherwise be filled with silence or children playing alone. These playful interactions form a foundation for children's social-emotional-cognitive development (Hassinger-Das et al, 2018). In this paper, we present a case study of a university-community partnership integrating cross-age peer mentoring, positive youth development, and evidence from the learning sciences into a communitybased playful learning program (Karcher, 2009).…”
mentioning
confidence: 99%